Immigrant child poverty in Scandinavia: a panel data study - Taryn Ann Galloway; Björn Gustafsson; Peder J. Pedersen; Torun Österberg (Institute for the Study of Labor (IZA), 2009)
Immigrant and native child poverty in Denmark, Norway and Sweden 1993 to 2001 is investigated using large sets of panel data. While native children face yearly poverty risks of less than 10 percent in all three countries and for all years investigated the increasing proportion of immigrant children with an origin in middle and low income countries have poverty risks that varies from 38 and up to as much as 58 percent. At the end of the observation period one third of the poor children in Norway have an immigrant origin, and that corresponding proportion is as high as about a half in Denmark as well as in Sweden. The strong overrepresentation of immigrant children from low and middle income countries when measured in yearly data is also found when applying a longer accounting period. We find that child poverty rates are generally high shortly after arrival to the new country, and typically decreases with years since immigration. Multivariate analysis shows that parents years since immigration and education affect risks of the number of periods in persistent poverty. While a native child is very unlikely to spend nine years in poverty, the corresponding risk for a child to a newly arrived immigrant from Turkey was found to be far from negligible. Much of the pattern is similar across the three countries but there are also some differences.
urn:nbn:de:101:1-20090622147
Keywords: F22; I32; J15; 330; Child poverty; immigration; Denmark; Norway; Sweden; Kinder; Armut; Migranten; Nordeuropa